2000
DOI: 10.1038/sj.ejcn.1600890
|View full text |Cite
|
Sign up to set email alerts
|

Age patterns in stunting and anaemia in African schoolchildren: a cross-sectional study in Tanzania

Abstract: Objective: To describe the nutritional status of schoolchildren from a rural area of Tanzania, with a particular emphasis on older adolescents to determine the timing of the growth spurt and differences by sex. Design: A cross-sectional survey using a randomly selected sample. Subjects: Six thousand eight hundred and one children aged 7 ± 18 y randomly selected from those enrolled in standards 2 ± 5 in 59 primary schools in Magu District, Tanzania. Results: Overall, 52.5% of children were stunted and 43.0% wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
70
4
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 10 publications
13
70
4
1
Order By: Relevance
“…Moreover, patterns observed among school-age populations are similar to those reported at younger ages (Wamani et al, 2007). With regard to age, several studies have reported a dramatic increase in stunting among older children (Stoltzfus et al, 1997;Lwambo et al, 2000;Goon et al, 2011;Senbanjo et al, 2011) demonstrating that linear growth continues to falter throughout the school-age years (The Partnership for Child Development, 1998). Mendez and Adair (1999) found that children who started school at earlier ages (5 or 6 years) were substantially taller than children who started school later (7 or 8 years) so it may be that better-off children enrol in school at earlier ages.…”
Section: Introductionsupporting
confidence: 48%
See 2 more Smart Citations
“…Moreover, patterns observed among school-age populations are similar to those reported at younger ages (Wamani et al, 2007). With regard to age, several studies have reported a dramatic increase in stunting among older children (Stoltzfus et al, 1997;Lwambo et al, 2000;Goon et al, 2011;Senbanjo et al, 2011) demonstrating that linear growth continues to falter throughout the school-age years (The Partnership for Child Development, 1998). Mendez and Adair (1999) found that children who started school at earlier ages (5 or 6 years) were substantially taller than children who started school later (7 or 8 years) so it may be that better-off children enrol in school at earlier ages.…”
Section: Introductionsupporting
confidence: 48%
“…Nutrition mediates outcome at school-age Lwambo et al, 2000;Goon et al, 2011;Senbanjo et al, 2011) demonstrating that linear growth continues to falter throughout the school-age years (The Partnership for Child Development, 1998). Mendez and Adair (1999) found that children who started school at earlier ages (5 or 6 years) were substantially taller than children who started school later (7 or 8 years) so it may be that better-off children enrol in school at earlier ages.…”
Section: Human Neurosciencementioning
confidence: 99%
See 1 more Smart Citation
“…The data presented in Fig. 2 for children in four countries show an apparent increase in haemoglobin with age for both sexes until around 14 years old, a trend that has already been reported for schoolchildren in the lake region of Tanzania 7 . At around 14 years of age, the mean haemoglobin concentrations of boys and girls in Kenya, Malawi and at the lakeshore site in Tanzania 6 tend to diverge.…”
Section: Discussionmentioning
confidence: 77%
“…While these achievements are encouraging, sustainable results are not expected if the nutritional status of adolescent girls is neglected. Regardless of the scientific reports of high rates of adolescent undernutrition from the developing world (6,(19)(20)(21)(22)(23)(24), adolescents have been considered low risk groups for health and nutrition. This has further been complicated by the absence of local reference data and difficulty of interpreting anthropometric data in this age group.…”
Section: Discussionmentioning
confidence: 99%